MARKETING COMMUNICATION STRATEGY OF PROMISE SOUL COFFEE THROUGH SOCIAL MEDIA POST PANDEMI COVID-19 - Gita Hapsari; Narni Narni; Dani Pramudya; Septian Tri Saputra; Reimond Hasangapan Mikkael (SEAN Institute, 2023)
This researcher aims to analyze the Marketing Communication Strategy of Janji Jiwa Coffee Through Social Media After the Covid-19 Pandemic. This research was studied using qualitative methods with descriptive research types. Data collection was carried out using a mix method, including interviews, documentation, observation, and strategies. Marketing communications through social media after the Covid pandemic has been proven to have sustainable effectiveness. This can be seen from the use of Social Media such as Instagram, the Janji Jiwa application, and ordering through Shoppee, Grab and Gojek which are collaborations with the Kopi Janji Jiwa company which makes it easier for people to consume Kopi Janji Jiwa. because of access such as the selection of types of drinks and food that are easily seen from the media. without any time and time limits. This shows that the Marketing Communication Strategy Through Social Media After the Covid-19 Pandemic is still being used today.